Frequency regulation in a microgrid integrating redox flow battery by utilizing an optimal predictive control approach - Khokhar, Bhuvnesh; Singh Parmar, K. P. (Electrical engineering, 2024)
When considering the frequency stability issues brought on by load shifts in a microgrid ( μ G) due to a significant integration of fluctuating renewable energy source-based generators and an inherent low inertia, energy storage units (ESUs) are unavoidable. The ESUs can immediately charge or discharge to make up for any shifts in load in the μ G since they react more quickly. This research investigates how a redox flow battery unit (RFBU) impacts the dynamic responses of a standalone μ G (S μ G) in this respect. As the secondary controller, an optimal intelligent model predictive control (iMPC) approach is presented. The cyclical parthenogenesis algorithm is implemented to improve the tuning parameter ( τ w ) in the iMPC cost function to demonstrate an optimal performance of the recommended control approach. The effectiveness of the iMPC approach is contrasted with that of other well-known control approaches. The simulation findings clearly demonstrate the impact of RFBU integration in the S μ G and the capability of the recommended iMPC approach in terms of improved dynamic responses and their transient characteristics. As a consequence, the peak value of the S μ G dynamic response improves by 70.53%, and the settling time improves by 82.26%. The suggested control approach’s sensitivity to the S μ G parametric uncertainties is also justified. The closed-loop stability of the suggested approach is also established. The effectiveness of the proposed iMPC approach and the impact of the RFBU integration are then confirmed by statistical analysis.